Determinants of GRDP and Rupiah Exchange Rate on Sharia Bank MSME Financing in Jambi Province 2010-2017 - Agusriandi -; Victor Diwantara; Syahril Ahmad; Saijun - (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2023)
The purpose of this study is to determine what factors influence the behavioral intentions of Banten's millennial generation toward halal tourism following the Covid-19 pandemic. This study modifies the Theory of Planned Behavior (TPB), intending to understand how intense religiosity affects the behavioral intentions of the Banten millennial generation toward halal tourism. Respondents in this study were millennials from 8 regencies and cities in the province of Banten. The number of respondents in this study amounted to 375 people. Questionnaires were distributed via Google form to respondents who met the inclusion criteria. The analytical method uses multiple linear regression to examine the effect of the independent variables on the dependent variable. The study's findings indicate that attitudes, subjective norms, and Islamic religiosity have a favorable and significant effect on behavioral intentions in halal tourism. At the indicated significance level, the variable Perceived behavioral control had no positive and significant effect on behavioral intentions in halal tourism. However, simultaneously all independent variables have a positive and significant effect on the behavioral intention of the Banten millennial generation on halal tourism. The study's findings indicate that attitudes, subjective norms, and Islamic religiosity have a favorable and significant effect on behavioral intentions in halal tourism. At the indicated significance level, the variable Perceived behavioral control had no positive and significant effect on behavioral intentions in halal tourism. However, all independent variables had a favorable and substantial effect on the behavioral intention of the Banten millennial generation toward halal tourism at the same time.